Static and fatigue performance of resin injected bolts for a slip and fatigue resistant connection in FRP bridge engineering. (August 2016) - Zafari, Behrouz; Qureshi, Jawed; Mottram, J. Toby; Rusev, Rusi
Abstract: This paper presents test results to evaluate the slip and fatigue performance of Resin Injected Bolted Joints (RIBJs) for pultruded Fibre Reinforced Polymer (FRP) material. The objective of the test series is to provide a robust method of connection for structural engineering that is both fatigue and slip resistant. Forty-six joints (using 23 specimens) were subjected to either static or combined static/cyclic loading at ambient room temperature. Ten specimens (five batches of two) had bolted connections without injected resin and were included to provide baseline static joint strengths. Sikadur®-30 and RenGel®-SW404 were the two cold-curing epoxy based resins used to fabricate the 13 RIBJ specimens. Testing was conducted with double lap-shear joints in accordance with modified guidance from Annex G and Annex K in standard BS EN 1090-2:2008. The specimen's geometry was established using this British Standard and an American Society of Civil Engineers pre-standard for pultruded thin-walled structures. Rectangular plates for the lap joints were cut from either a wide flange section of size 254 × 254 × 9.53 mm or a flat sheet of 6.35 mm thickness. Bolting was with either M16 or M20 steel threaded bolts of Grade 8.8. Sixteen specimens, for eight batches of two specimens were failed in a short duration for static strength. Four RIBJ specimens had static load cycling to an assumed service load level. Three specimens out of 23 were subjected to stage static and cyclic fatigue loadings to determine stiffness changes, life-time 'slip' load and residual joint strength. The reported results are evaluated for slip and fatigue performance and the main finding is that resin injection shows much promise as a mechanical method of connection in pultruded FRP structures.